Efektivitas Project Based Learning Model Melalui Proyek PKA-KKA Dalam Pembelajaran Audit Internal di Diklat JFA Ahli Polri - Mustofa - Kamal (Universitas Kristen Maranatha, 2018)
This action research aims to assess the effectiveness of internal audit learning in the education and training of internal police of the National Police through project based learning models. The project was chosen with consideration; there is a gap between the conditions of 24 training participants from the role of law enforcement (watchdog) and new roles as candidates for internal auditors (assurance and consulting). The research method uses qualitative and quantitative.The project provided in the form of